FAKTOR YANG MEMPENGARUHI PERKEMBANGAN ANAK BALITA USIA 1-2 TAHUN DI KOTA BUKITTINGGI - Putri, Yelmi Reni; Lazdia, Wenny; Putri, Lola Oktriza Eka (Universitas Fort De Kock Bukittinggi, 2018)
The purpose of this research was to determine the some factors influence the development of toddlers in Community Health Center Plus MKS Bukittinggi in 2018. The type of this research was analytical descriptive with cross sectional study research design. The populations were all children under five years old (1-2 years old). Then, by using systematic random sampling technique, 73 people were chosen as the samples. The results of this research showed pregnancy were not good (abnormal) was around 64.1% (P= 0.049). Then, 64.1% of the respondents had abnormal labor complications development (P= 0.049). Next, nutritional fulfillment was not good with abnormal development was around 89.7% 9P =0,000). After that, 61.5% of them done bad health care with abnormal development (P=0.045). Last, the susceptibility to disease exists with abnormal development was around 69.2% with p-value of 0.035. In short, it can be concluded that pregnancy condition, complications of childbirth, fulfillment of nutrition, health care, and susceptibility to diseases were some factors related to developmental disorders of toddler. Then, the most significant variables was the fulfillment of nutrients with P = 0,000. Moreover, it is expected to the health officers, especially the midwives, improve their monitoring to the growth and development of toddler.Keywords: Pregnancy Conditions, Labor Complications, Nutrition Compliance, Health Care, Susceptibility to Disease